Huge Primary Parasitic Leiomyoma in a Postmenopausal Lady: A Rare Presentation - Nkencho Osegi; E. Yilaiba Oku; C. Stanley Uwaezuoke; K. Timothy Alawode; S. Adeniyi Afolabi (Case Reports in Obstetrics and Gynecology)
Although uterine myomas are the most common benign tumours of the female pelvis in the reproductive age group, they rarely grow in menopausal women. Parasitic fibroids without prior history of laparoscopic myomectomy are even a rarer presentation particularly in menopausal women. The case presented is a 58-year-old grand-multiparous, menopausal lady with progressive abdominal swelling of three-year duration. She had excision of a huge parasitic fibroid attached to omentum. She had partial omentectomy, total abdominal hysterectomy, and bilateral salpingo-oophorectomy. The parasitic fibroid mass weighed 5.2kg and histopathology confirmed leiomyoma uteri with cystic degeneration and lymph nodes with reactive lymphoid hyperplasia. She had uneventful postoperative recovery and follow-up has so far been uneventful.